A genetic program promotes C. elegans longevity at cold temperatures via a thermosensitive TRP channel - Xiao, Rui (2013)
Both poikilotherms and homeotherms live longer at lower body temperatures, highlighting a general role of temperature reduction in lifespan extension. However, the underlying mechanisms remain unclear. One prominent model is that cold temperatures reduce the rate of chemical reactions, thereby slowing the rate of aging. This view suggests that cold-dependent lifespan extension is simply a passive thermodynamic process. Here, we challenge this view in C. elegans by showing that genetic programs actively promote longevity at cold temperatures. We find that TRPA-1, a cold-sensitive TRP channel, detects temperature drop in the environment to extend lifespan. This effect requires cold-induced, TRPA-1-mediated calcium influx and a calcium-sensitive PKC which signals to the transcription factor DAF-16/FOXO. Human TRPA1 can functionally substitute for worm TRPA-1 in promoting longevity. Our results reveal a new function for TRP channels, link calcium signaling to longevity, and importantly, demonstrate that genetic programs contribute to lifespan extension at cold temperatures.